Determinants of health behaviors of physical education teachers and students - Paweł F. Nowak; Magdalena Lelonek; Edyta Suliga; Łukasz Choła (Nofer Institute of Occupational Medicine, 2024)
Background The level of health behavior of physical education teachers and people preparing to perform this profession is important from the point of view of the need to play the role of a health promoter - an authority in the promotion of health culture. The aim of the study was to assess the level of teachers' health behaviors of physical education teachers and students, as well as to search for their determinants. Material and Methods The research covered 127 teachers and 173 physical education students. Standardized questionnaire tools were used to assess the level of health behaviors ( Juczyński Health Behavior Inventory ) and physical activity ( International Physical Activity Questionnaire ). Results Teachers demonstrate a higher level of health behaviors than students. Most respondents achieved an average level of the general health behavior index (HBI) (53.1% of teachers, 52.3% of students), while a high level - 26.8% of teachers, 19.8% of students and a low level - 19.9% of teachers and 27.7% of students. Female gender and teaching profession are significant predictors of HBI. Physical activity, both its current level and the level undertaken in the past, as well as the body mass index (BMI) do not determine HBI. In the regression model, physical activity is significantly associated with male gender, past sports activity and a lower BMI level. Conclusions Research indicates neglect in the general area of health behaviors among men, while among women, physical activity needs to be more widely popularized. The teacher education system should be more focused on the development of self-development competencies in the context of health-promoting behaviors. Med Pr Work Health Saf. 2024;75(4):355-365